New interpretation of the wings of the pterosaur Rhamphorhynchus muensteri based on the Zittel and Marsh specimens. (21st March 2016) - Bennett, S. Christopher
Abstract: The Zittel wing of Rhamphorhynchus muensteri is reinterpreted as preserving negative impressions of closely spaced broad flat actinofibrils that were replaced by calcite but were prepared away by the specimen's finder. The Marsh specimen preserves positive impressions of the dorsal and ventral surfaces of the wing, which show that the skin was smooth with fine wrinkles and that actinofibrils were not on the wing surface. Based on comparisons of those specimens, the dactylopatagium consisted of dorsal and ventral skins of epidermis and dermis surrounding a common hypodermis core, and keratinous actinofibrils developed in place within the dorsal epidermis adjacent to a layer of linear collagen fibers in the dorsal dermis. The actinofibrils and linear collagen fibers together formed the main functional structure of the dactylopatagium. That structure made the dactylopatagium somewhat stiff and essentially inextensible so that it folded up along discrete fold lines that probably were genetically determined. A pneumatic retrophalangeal wedge behind the antebrachium through at least wing phalanx 3 streamlined the transition between the thick wing spar and thin patagium.